Comparison of orthopantomogram and lateral cephalogram for mandibular measurements - S Saravana Kumar; V Thailavathy; Daya Srinivasan; Divya Loganathan; J Yamini (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of the present study is to clarify the possible application of orthopantomogram (OPG) for evaluating craniofacial specifications such as angular and linear measurements of the mandible by comparing with lateral cephalogram. Materials and Methods: OPG and lateral cephalogram were taken from 100 patients of age group 16-35 years from Chettinad Dental College and Research Institute. Linear measurements (body length and ramus height) and angular measurement (gonial angle) were assessed both in lateral cephalogram and OPG. Independent t-test was performed for comparison of OPG and lateral cephalogram using SPSS with a probability level of P < 0.05 considered to be statistically significant. Results: The results of the present study show that there is no statistically significant difference in ramus height and gonial angle when compared between OPG and lateral cephalogram while statistically significant difference exists for body length between OPG and lateral cephalogram. Conclusion: It may be concluded that panoramic radiography can be used to determine the gonial angle and ramus height as accurately as a lateral cephalogram. However, clinicians should be vigilant when predicting horizontal measurement from OPGs.